Picture of Dorian Gray : authoritative texts, backgrounds, reviews and reactions, criticism - Wilde, Oscar; Gillespie, Michael Patrick (ed.)
"First published in 1890 in Lippincott's Monthly Magazine, The Picture of Dorian Gray was released as a revised book in 1891. This Norton Critical Edition includes both the 1890 and 1891 editions. As a work of fiction, the novel is an exploration of artistic hedonism, inspiration, and intensity. This edition allows readers to compare the two texts of Dorian Gray and better understand the book's contemporary reception, debate, and criticism. "Backgrounds" allows readers to consider the correspondence between Oscar Wilde and his critics, and the heated public debate over art and morality that the novel engendered. "Criticism" includes essays on the aesthetics, modernity, characters, and subplots within the novel--and demonstrates the changing interpretations of the novel over time. A Chronology and Selected Bibliography are also included"--
Includes bibliographical references.
Keywords: Wilde, Oscar; Appearance (Philosophy); Conduct of life; Portraits